RATIONAL DISTRIBUTION OF FLOWS ON THE NETWORK - Bosov, A. A.; Bekh, P. V. (Science and Transport Progress, 2006)
The article offers a method of selecting a rational route of freights delivery by rail by means of vectoral optimization.